IMNU DIGITAL BOARDING SCHOOL: CAMPAIGNING DIGITAL MEDIA AND BUSINESS TO THE ISLAMIC YOUTH - Muhamad Husni Mubarok (International Journal of Social Science, 2023)
Digital media and business are rapidly growth. IMNU has a willingness to improve digital individuals' skills. They try to campaign using social media platforms and face-to-face workshops. explore the role of IMNU in implementing strategic campaigns of digital and business media. The research is a descriptive qualitative study in which participant observation is the primary data. The result shows that IMNU campaign consists of three categories: training, tutorials, and practitioners' sharing experiences on social media. They also present face-to-face digital training or workshop in NU-based Islamic boarding schools throughout Indonesia. The existence of IMNU has become important to help Islamic youth in developing their digital skill and accompanying them to provide knowledge on digital literacy